Kartki z podróży do Puław Bolesława Prusa jako sprawdzian ludzkiej (nie)uważności - Pocheć, Ewelina (Colloquia Litteraria, 2023)
The paper is dedicated to the issue of humans (un)attention category in the contex of journey situation in one of the reportage work by Bolesław Prus. In the reception of reportage the theory of presence is inextricably associated with category of attention. Author of the article shows possibility of analyze Bolesław Prus work in the context of Janina Brach-Czaina philosophy and modern trends in the field of non-anthropocentric humanities.